2018
DOI: 10.1111/xen.12442
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term safety outcome of systemic immunosuppression in pig‐to‐nonhuman primate corneal xenotransplantation

Abstract: Costimulatory blockade-based and anti-CD20 antibody/tacrolimus-based immunosuppressive therapies seem to be comparably safe with steroid therapy in nonhuman primates receiving corneal xenotransplantation, as they did not reactivate Rhesus Cytomegalovirus and maintained manageable systemic status. Although reactivation is rare, antiviral prophylaxis for simian varicella virus should be considered in immunocompromised hosts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 38 publications
(77 reference statements)
0
23
0
Order By: Relevance
“…One recent study satisfied the success criteria of IXA consensus statements on conditions for clinical trials of cornea xenotransplantation in a PKP model using anti‐CD40 or anti‐CD20 antibody‐based immunosuppression, one of which used clinically applicable drugs including anti‐CD20 antibody, basiliximab, and tacrolimus (Figure ) . They also confirmed the safety of the anti‐CD20 antibody‐based immunosuppression by showing that NHP recipients generally maintained a good condition without serious complications during the follow‐up period . Importantly, they cautiously suggested that the close monitoring of immunosuppression‐associated complications and infection prophylaxis should be included in the protocol for conducting a cornea xenotransplantation clinical trial using potent immunosuppression.…”
Section: Research Activities In Xenotransplantationmentioning
confidence: 82%
See 2 more Smart Citations
“…One recent study satisfied the success criteria of IXA consensus statements on conditions for clinical trials of cornea xenotransplantation in a PKP model using anti‐CD40 or anti‐CD20 antibody‐based immunosuppression, one of which used clinically applicable drugs including anti‐CD20 antibody, basiliximab, and tacrolimus (Figure ) . They also confirmed the safety of the anti‐CD20 antibody‐based immunosuppression by showing that NHP recipients generally maintained a good condition without serious complications during the follow‐up period . Importantly, they cautiously suggested that the close monitoring of immunosuppression‐associated complications and infection prophylaxis should be included in the protocol for conducting a cornea xenotransplantation clinical trial using potent immunosuppression.…”
Section: Research Activities In Xenotransplantationmentioning
confidence: 82%
“…3) died suddenly due to an accident during sampling. However, the graft was transparent (adopted fromreference )…”
Section: Research Activities In Xenotransplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 2010 and 2018, 38 rhesus macaques which had undergone full‐thickness porcine corneal xenotransplantation were included . Among them, four NHPs dying within 3 months without graft rejection were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Choi et al further explain the quantification of infectious risks by investigating the lasting impact of immunosuppression techniques on porcine cornea recipients. They look into hematological, biochemical, and supportive assays to analyze reactivation of viruses in Chinese rhesus macaques.…”
Section: New Testsmentioning
confidence: 99%